2016
DOI: 10.3389/fpsyg.2016.01851
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Group Schema Therapy for Outpatients with Severe Borderline Personality Disorder in Germany: A Pilot Study with Three Year Follow-Up

Abstract: Borderline Personality Disorder (BPD) is a severe, challenging to treat mental disorder. Schema therapy (ST) as an individual therapy has been proven to be an effective psychological treatment for BPD. A group format of ST (GST) has been developed and evaluated in a randomized controlled trial in the United States and piloted in The Netherlands. These results suggest that GST speeds up and amplifies treatment effects of ST and might reduce delivery costs. However, feasibility in the German health care system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Evidence-based treatments for BPD, e.g., dialectical-behavioral therapy (DBT), schema-focused therapy (SFT), and mentalization-based therapy (MBT) utilize group components. Its beneficial effects on social perception and interpersonal skills in various settings, e.g., outpatient and inpatient treatment, have been outlined ( Farrell et al, 2009 ; Bateman and Fonagy, 2010 ; Bloom et al, 2012 ; Karterud and Bateman, 2012 ; Laurenssen et al, 2014 ; Kvarstein et al, 2015 ; Linehan and Wilks, 2015 ; Dimaggio and Brune, 2016 ; Fassbinder et al, 2016 ; Kramer et al, 2016 ; Antonsen et al, 2017 ; Edel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based treatments for BPD, e.g., dialectical-behavioral therapy (DBT), schema-focused therapy (SFT), and mentalization-based therapy (MBT) utilize group components. Its beneficial effects on social perception and interpersonal skills in various settings, e.g., outpatient and inpatient treatment, have been outlined ( Farrell et al, 2009 ; Bateman and Fonagy, 2010 ; Bloom et al, 2012 ; Karterud and Bateman, 2012 ; Laurenssen et al, 2014 ; Kvarstein et al, 2015 ; Linehan and Wilks, 2015 ; Dimaggio and Brune, 2016 ; Fassbinder et al, 2016 ; Kramer et al, 2016 ; Antonsen et al, 2017 ; Edel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PRO*BPD study is performed in the outpatient clinic of the Department of Psychiatry and Psychotherapy at Lübeck University, Germany. The Department of Psychiatry treats more than 450 BPD patients/year (internal statistics) and has extensive experience in treating and researching BPD [ 48 , 55 , 57 59 ]. DBT has been used in Lübeck since 1999, while ST has been offered since 2009.…”
Section: Method/designmentioning
confidence: 99%
“…A group format (Group schema therapy, GST) was developed by Farrell and Shaw [ 52 ] and was successfully tested in an RCT in the United States: Patients who received GST showed no drop-out, high BPD remission rates, significant reductions in BPD-typical and general psychiatric symptoms as well as improvements in psychosocial functioning, with large effect sizes after only 8 months. Two outpatient pilot studies on GST in the Netherlands [ 47 ] and Germany [ 48 ] used GST in combination with individual ST and found substantial improvements in BPD-symptoms, general psychopathology, quality of life and happiness. To systematically investigate the clinical effectiveness and cost-effectiveness of GST for BPD and to test different formats of GST (GST only vs. a combination of GST with individual ST), a large, international, multicenter RCT on GST for BPD is currently in progress [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results validated that in-patient schema therapy can significantly reduce symptoms of severe BPD and global severity of psychopathology. A number of more recent studies have also demonstrated significant symptom reduction following GST whether in a short-term GST in-patient programme (Nenadić et al, 2017), in an out-patient programme lasting a year (Fassbinder et al, 2016), or in an out-patient programme of just 20 sessions (Skewes et al, 2015). However, in all three of these studies, there was no allocation to a no-treatment control or other treatment comparison condition.…”
Section: Group Schema Therapy For Borderline Personality Disordermentioning
confidence: 99%